Modified Runoff Curve Numbers for Arid Rhyolite Basins - Sharma, K D; Vangani, N S; Kalla, A K (Annals of Arid Zone, 2016)
Runoff curve numbers (CN) for rhyolite basins in the Indian arid zonewere derved from rainfall and runoff data recorded over a period of 5 years from 1975-1979. As against the Soil Conservation Service Hand Book values of90-92. the actual optimized CN was found to be 74, indicating a lesser volume of runoff from these basins than estimated by the SCS method. The hand book CN value overpredicted runoff by 31 to 54% for storms> 100 mm, and by 88 to 267% fer storms